2017
DOI: 10.1016/j.addbeh.2016.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Associations between PTSD and intimate partner and non-partner aggression among substance using veterans in specialty mental health

Abstract: Background Risk factors of violence perpetration in veterans include substance use and posttraumatic stress disorder (PTSD); however, it is unknown whether these factors are associated with greater risk for partner or non-partner violence. This study investigated the associations between probable PTSD, heavy drinking, marijuana use, cocaine use, and partner and non-partner violence perpetration. Methods Self-report questionnaires assessing past-year partner and non-partner aggression (CTS2) as well as past-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…The majority ( n = 31) of included studies reported past-year IPV perpetration ( Buchholz et al, 2017 ; Byrne & Riggs, 1996 ; Dutra, de Blank, Scheiderer, & Taft, 2012 ; Fonesca et al, 2006 ; Foran et al, 2011 ; Forgey & Badger, 2006 ; Gerlock, Szarka, Cox, & Harel, 2016 ; Gondolf & Foster, 1991 ; Heavey, Homish, Goodell, & Homish, 2017 ; Heyman & Neidig, 1999 ; Hiley-Young, Blake, Abueg, Rozynko, & Gusman, 1995 ; Hundt & Holohan, 2012 ; Kar & O'Leary, 2013 ; Kelley, Stambaugh, Milletich, Veprinsky, & Snell, 2015 ; Klaw, Demers, & Da Silva, 2016 ; McCarroll et al, 2010 ; Merrill, Crouch, Thomsen, Guimond, & Milner, 2005 ; Newby et al, 2003 ; Owens et al, 2013 ; Pan, Neidig, & O'Leary, 1994 ; Rosen, Knudson, et al, 2002 ; Rosen, Parmley, Knudson, & Fancher, 2002c ; Schmaling, Blume, & Russell, 2011 ; Sherman, Sautter, Jackson, Lyons, & Han, 2006 ; Slep, Foran, Heyman, & Snarr, 2011 ; Smith Slep, Foran, Heyman, & Snarr, 2010 ; Stander et al, 2011 ; Taft et al, 2009 ; Teten et al, 2010 ; Teten, Schumacher, Bailey, & Kent, 2009 ; Tharp, Sherman, Bowling, & Townsend, 2016 ). The remaining studies measuring IPV in different time periods (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority ( n = 31) of included studies reported past-year IPV perpetration ( Buchholz et al, 2017 ; Byrne & Riggs, 1996 ; Dutra, de Blank, Scheiderer, & Taft, 2012 ; Fonesca et al, 2006 ; Foran et al, 2011 ; Forgey & Badger, 2006 ; Gerlock, Szarka, Cox, & Harel, 2016 ; Gondolf & Foster, 1991 ; Heavey, Homish, Goodell, & Homish, 2017 ; Heyman & Neidig, 1999 ; Hiley-Young, Blake, Abueg, Rozynko, & Gusman, 1995 ; Hundt & Holohan, 2012 ; Kar & O'Leary, 2013 ; Kelley, Stambaugh, Milletich, Veprinsky, & Snell, 2015 ; Klaw, Demers, & Da Silva, 2016 ; McCarroll et al, 2010 ; Merrill, Crouch, Thomsen, Guimond, & Milner, 2005 ; Newby et al, 2003 ; Owens et al, 2013 ; Pan, Neidig, & O'Leary, 1994 ; Rosen, Knudson, et al, 2002 ; Rosen, Parmley, Knudson, & Fancher, 2002c ; Schmaling, Blume, & Russell, 2011 ; Sherman, Sautter, Jackson, Lyons, & Han, 2006 ; Slep, Foran, Heyman, & Snarr, 2011 ; Smith Slep, Foran, Heyman, & Snarr, 2010 ; Stander et al, 2011 ; Taft et al, 2009 ; Teten et al, 2010 ; Teten, Schumacher, Bailey, & Kent, 2009 ; Tharp, Sherman, Bowling, & Townsend, 2016 ). The remaining studies measuring IPV in different time periods (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies measured physical IPV perpetration among military populations with estimates ranging from 5.0%–57.6% ( Buchholz et al, 2017 ; Byrne & Riggs, 1996 ; Dutra et al, 2012 ; Foran et al, 2011 ; Forgey & Badger, 2006 ; Gerlock et al, 2016 ; Heavey et al, 2017 ; Hiley-Young et al, 1995 ; Hundt & Holohan, 2012 ; Kar & O'Leary, 2013 ; Kelley et al, 2015 ; Klaw et al, 2016 ; LaMotte et al, 2017 ; LaMotte, Taft, Reardon, & Miller, 2014 ; LaMotte, Taft, Weatherill, et al, 2014 ; Owens et al, 2013 ; Pan et al, 1994 ; Petrick et al, 1983 ; Portnoy et al, 2018 ; Rosen, Knudson, et al, 2002 ; Rosen, Parmley, et al, 2002c ; Sherman et al, 2006 ; Smith Slep et al, 2010 ; Stander et al, 2011 ; Taft et al, 2007 ; Taft et al, 2009 ; Teten et al, 2009 ; Teten et al, 2010 ; Tharp et al, 2016 ; Waliski et al, 2013 ; Zamorski & Wiens-Kinkaid, 2013 ). Fifteen studies were suitable for inclusion in a meta-analysis for past-year physical IPV with subgroup analysis by gender ( Foran et al, 2011 ; Forgey & Badger, 2006 ; Gerlock et al, 2016 ; Heavey et al, 2017 ; Hiley-Young et al, 1995 ; Hundt & Holohan, 2012 ; Kar & O'Leary, 2013 ; Klaw et al, 2016 ; Owens et al, 2013 ; Pan et al, 1994 ; Rosen, Knudson, et al, 2002 ; Rosen, Parmley, et al, 2002c ; Sherman et al, 2006 ; Smith Slep et al, 2010 ; Stander et al, 2011 ; Taft et al, 2009 ; Teten et al, 2009 ; Teten et al, 2010 ; …”
Section: Resultsmentioning
confidence: 99%
“…The link between IPA and PTSD may be particularly common in veterans [ 39 , 40 , 41 , 42 , 43 ]. This link was uncommon but nonetheless occurred among our interviewees.…”
Section: Four Levels Of Influencementioning
confidence: 99%
“…The sample (n=833) was primarily comprised of middle-aged Caucasian men from the larger study (Davis et al, 2016, Buchholz et al, 2016) who completed the gambling item (i.e., 6 participants had missing data and thus were excluded). A total of 288 (35%) participants gambled at least once during the 30 days prior to assessment.…”
Section: Resultsmentioning
confidence: 99%